Creating Aztlán : Chicano Art, Indigenous Sovereignty, and Lowriding Across Turtle Island - Miner, Dylan A. T., 1976- (Book collections on Project MUSE., 2014)
"Creating Aztlán interrogates the important role of Aztlán in Chicano and Indigenous art and culture. Using the idea that lowriding is an Indigenous way of being, author Dylan A.T. Miner (Metis) discusses the multiple roles that Aztlán has played at various moments in time, engaging pre-colonial indigeneities, alongside colonial, modern, and contemporary Xicano responses to colonization"--